Climate change and pulse migration: intermittent Chugach Inuit occupation of glacial fiords on the Kenai Coast, Alaska - Crowell, Aron L.; Arimitsu, Mayumi (Frontiers in Environmental Archaeology, 2023)
For millennia, Inuit peoples of the Arctic and Subarctic have been challenged by the impacts of climate change on the abundance of key subsistence species. Responses to climate-induced declines in animal populations included switching to alternative food sources and/or migrating to regions of greater availability. We examine these dynamics for the Chugach Inuit (Sugpiat) people of southern coastal Alaska by synthesizing a large body of evidence from archeological sites, including radiocarbon dates and archaeofaunal assemblages, and by applying contemporary knowledge of glaciomarine ecosystems, spatial patterns of resource richness, and ocean-climate induced regime shifts in the Gulf of Alaska. We hypothesize that Chugach groups migrated from Cook Inlet and Prince William Sound to the Kenai Peninsula during periods of low sea surface temperatures (SSTs) to harvest harbor seals, which were seasonally aggregated near tidewater glaciers during pupping season, as well as piscivorous seabirds, Pacific cod, and other species that thrive under cool ocean conditions. During warming phases, the Chugach returned to Cook Inlet and Prince William Sound to fish for salmon and other species that abound during higher SSTs. Drivers of this coupled human-natural system of repeated (pulse) migration include the Pacific Decadal Oscillation (PDO), the dominant pattern of sea surface temperatures in the North Pacific that has been shown to generate step-like regime shifts in the marine food web; and coastal glaciers that structure the functioning of fiord ecosystems and support high levels of biological productivity. The culturally-constructed Chugach niche in the glaciomarine habitat of the Gulf of Alaska was based on intergenerationally transmitted ecological knowledge that enabled a resilient, mobile response to climate and resource variation.